SISTEM PENGELOLAAN KEARSIPAN GOOGLE MELALUI BIG DATA: Array - Aldha Shafrielda Sihab; Anugerah Pagiyan Nurfajar (Jurnal Kearsipan, 2020)
This article examines the use of Big Data technology for the records and archives administration system in the contemporary era. Big Data can be defined as a collection of data that is extremely large and complex which cannot be dealt with the traditional data processing software. This technology makes it possible to store large amounts of data and can be accessed quickly. By implication, Big Data served sufficiently as a digital records and archives administration system. One of companies in the world that uses Big Data as a digital system is Google. Inc. This phenomenon is quite new in the contemporary era, hence it is quite interesting to see "how Google manages its records and archives administration system through Big Data". In line with the previous question, this article aims to find out how Google manages its records and archives administration system through Big Data. This article uses a qualitative research method through the literature review. The data used in this article is from the secondary data sourced from books and journal articles. One of the important findings in this article is that Google uses a distributed storage system to manage structured data called Bigtable. Bigtable makes the other Google services operate, so it can be stated that Bigtable is a fundamental system in Google. Although there are quite a few Google services which use Bigtable as the base, there are three main services that everyone use the most, namely Google Analytics, Google Earth, and Personalize Search. Through this Big Data technology, it can be seen that the archive management can use not only the conventional methods, but also the latest technology.